Short-term forecasting economic activity in Germany: A supply and demand side system of bridge equations - Nicolas Pinkwart (Deutsche Bundesbank, 2018)
We present a comprehensive disaggregate approach for short-term forecasting economic activity in Germany by explicitly taking into account the supply or production side and the demand side of GDP. The GDP figures calculated by the two sides usually yield different results and the official GDP release is somewhere in between. We make use of this statistical procedure by separately modeling the two sides of GDP in a system of bridge equations at the most disaggregate level available and combining the resulting two aggregate GDP forecasts. Comparing several specification schemes in an out-of-sample forecast evaluation setup, we are able to find informative forecasts for most of the underlying GDP components. We then show first, that both approaches already yield informative aggregate forecasts for forecast horizons of up to 28 weeks and second, that combining the production side and the demand side projections substantially improves the forecast performance, in particular for the shorter forecast horizons.
Keywords: C22; C53; E32; E37; 330; German Economy; GDP; Disaggregation; Forecasting; Nowcasting; Bridge Equations